Arginase I Release from Activated Neutrophils Induces Peripheral Immunosuppression in a Murine Model of Stroke. Issue 10 (October 2015) - Sippel, Trisha R; Shimizu, Takeru; Strnad, Frank; Traystman, Richard J; Herson, Paco S; Waziri, Allen
Transient suppression of peripheral immunity is a major source of complication for patients suffering from ischemic stroke. The release of Arginase I (ArgI) from activated neutrophils has recently been associated with T-cell dysfunction in a number of pathologies. However, this pathway has not been previously explored in ischemic stroke. Using the murine model of transient middle cerebral artery occlusion, we explored effects of stroke on peripheral T-cell function and evaluated the role of neutrophils and ArgI. Stimulation of splenic T cells from post-stroke animals with anti-CD3/CD28 resulted in decreased proliferation and interferon-γ production when compared with sham-surgery controls. Flow cytometric analysis of intrasplenic leukocytes exposed the presence of a transient population of activated neutrophils that correlated quantitatively with elevated ArgI levels in culture media. In vitro activation of purified resting neutrophils from unmanipulated controls confirmed the capacity for murine neutrophils to release ArgI from preformed granules. We observed decreased expression of the L-arg-sensitive CD3ζ on T cells, consistent with decreased functional activity. Critically, L-arg supplementation restored the functional response of post-stroke T cells to mitogenic stimulation. Together, these data outline a novel mechanism of reversible, neutrophil-mediated peripheral immunosuppression related to ArgI release following ischemic stroke.